RANCANG BANGUN SISTEM INFORMASI PENYALUR DANA BANTUAN SISWA ( BOS ) BERBASIS WEB - Harfizar Harfizar; Fauzan Manafi Albar; Muh Afiffudin (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
Application of Information Technology has now spread almost in all fields is no exception in the management of the School Operational Fund allows all operational funds management activities informasi.Kebutuhan technology will utilize information technology is closely connected with the role of fund management boss as a standard program of education that is needed to finance the activities nonpersonnel operation for 1 ( one ) year as part of the overall education funding to education units can conduct educational activities on a regular and ongoing basis in accordance with National Education Standards . With the construction of Management Information Systems Applications " ASISMEN " School Operational Assistance " BOS " , which can provide information to the school principal and school treasurer or educational institutions regarding the distribution of financial problems by the BOS . So that the information provided is presented in the form of special reports that can be presented properly and periodically easily understood and easy to use. One example is the implementation of financial information systems in enterprises or other institutions , as well as in SDN Tangerang The final result of this research is a system that can provide accurate and up to date report that meets the objectives of the national education standard 8 set by the central government.